1997
DOI: 10.1101/gad.11.11.1422
|View full text |Cite
|
Sign up to set email alerts
|

The an11 locus controlling flower pigmentation in petunia encodes a novel WD-repeat protein conserved in yeast, plants, and animals.

Abstract: In petunia flowers, the loci anl, an2, and anll control the pigmentation of the flower by stimulating the transcription of anthocyanin biosynthetic genes. The anl and an2 locus were recently cloned and encode a basic helix-loop-helix (bHLH) and MYB-domain transcriptional activator, respectively. Here, we report the isolation of the anll locus by transposon tagging. RNA gel blot experiments show that anll is expressed independently from anl and an2 throughout plant development, as well as in tissues that do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
310
1
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(335 citation statements)
references
References 50 publications
(50 reference statements)
19
310
1
5
Order By: Relevance
“…Although we have shown that ODO1 is capable of activating the EPSPS promoter directly ( Figure 5C), it remains to be investigated whether ODO1 interacts with specific sequences in promoters either alone or in concert with other regulatory proteins or whether it influences the activity of other transcription factors. Perhaps it would be useful to focus on anthocyanin biosynthesis in petunia petals, which is regulated by the R2R3-type MYB AN2, the basic-helix-loop-helix-protein AN1, and the WD40 protein AN11 (De Vetten et al, 1997;Spelt et al, 2000Spelt et al, , 2002. The transcriptional network controlling scent production and emission can now be investigated using ODO1 as a starting point.…”
Section: Color and Scent Production Occur At Different Developmentalmentioning
confidence: 99%
“…Although we have shown that ODO1 is capable of activating the EPSPS promoter directly ( Figure 5C), it remains to be investigated whether ODO1 interacts with specific sequences in promoters either alone or in concert with other regulatory proteins or whether it influences the activity of other transcription factors. Perhaps it would be useful to focus on anthocyanin biosynthesis in petunia petals, which is regulated by the R2R3-type MYB AN2, the basic-helix-loop-helix-protein AN1, and the WD40 protein AN11 (De Vetten et al, 1997;Spelt et al, 2000Spelt et al, , 2002. The transcriptional network controlling scent production and emission can now be investigated using ODO1 as a starting point.…”
Section: Color and Scent Production Occur At Different Developmentalmentioning
confidence: 99%
“…The an11 locus encodes a highly conserved WD40 repeat protein that is localized in the cytosol. Because an11 Ϫ mutants can be rescued, at least partially, by overexpression of AN2, we previously suggested that AN11 may post-translationally regulate the activity of the anthocyanin transcription factors by an as yet unknown mechanism (de Vetten et al, 1997). The observation that mutation of the Arabidopsis transparent testa glabra ( ttg ) gene, encoding a homologous WD40 protein (Walker et al, 1999), can be complemented by (over)expression of R1 from maize points in the same direction (Lloyd et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Transient expression assays were performed by particle bombardment of petunia W115 leaves, as described previously (de Vetten et al, 1997;Quattrocchio et al, 1998) …”
Section: Expression Analysesmentioning
confidence: 99%
“…PhAN1, PhAN2 and PhAN11 are genes controlling both pigmentation and vacuolar pH in petunia petals. 8,9,10 Petunia also has a series of PhPH genes regulating vacuolar pH in the petals. 11,12,13 Because anthocyanins are accumulated in the vacuole and their colors change with pH (reddish at lower pH and bluish at higher pH), the PhPH genes also regulate petal color.…”
Section: Five Genes Affecting Anthocyanin Colormentioning
confidence: 99%